2011
DOI: 10.1007/s11356-011-0570-9
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, dioxin-like activities, and endocrine effects of DDT metabolites—DDA, DDMU, DDMS, and DDCN

Abstract: Our results clearly point out the need to integrate the potential ecotoxicological risks associated with the "neglected" p,p'-DDT metabolites. For instance, these DDT metabolites should be integrated into sediment risk assessment initiatives in contaminated areas. One major challenge would be the identification of baseline data for such risk assessment. Further studies are also warranted to determine possible additive, synergistic, or antagonistic effects that may interfere with the fundamental cytotoxicity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 80 publications
0
19
0
1
Order By: Relevance
“…For example, 2-chloro-1, 1-bis(4-chlorophenyl)ethylene (DDMU), 2,2-bis(4-chlorophenyl)ethanol (DDOH), bis(4-chlorophenyl)ketone (DBP), and 4,4′-dichlorodiphenylmethane (DDM) are important intermediary metabolites of DDT (Faroon and Harris 2002). Toxicity test showed that some of these DDT metabolites have cytotoxic and estrogenic activities (Wetterauer et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, 2-chloro-1, 1-bis(4-chlorophenyl)ethylene (DDMU), 2,2-bis(4-chlorophenyl)ethanol (DDOH), bis(4-chlorophenyl)ketone (DBP), and 4,4′-dichlorodiphenylmethane (DDM) are important intermediary metabolites of DDT (Faroon and Harris 2002). Toxicity test showed that some of these DDT metabolites have cytotoxic and estrogenic activities (Wetterauer et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…DDT might reduce (Rogan and Gladen, 1985;Rogan et al, 1987;Gladen and Rogan, 1995;Kostyniak et al, 1999), lengthen (Weldon et al, 2006) or have no effect (Cupul-Uicab et al, 2008) on duration of lactation, due to the endocrine disruptive properties of DDT isomers and breakdown products (Wetterauer et al, 2012). The levels of DDT in SA are exceedingly high -the highest yet measured was 59.3 mg/kg ΣDDT mf (milk fat) (Bouwman et al, 1990a).…”
Section: Introductionmentioning
confidence: 99%
“…The sites at Barby and Magdeburg receive substantial amounts of waste water via the river Saale from the cities Leipzig and Halle [5]. In accordance with this finding, several studies report the contamination of the river Elbe or its tributaries with (xeno)estrogens such as 4-alkylphenols, 4-alkylphenol ethoxylates, 4-alkylphenoxy carboxylates, bisphenol A, and dichlorodiphenyltrichloroethane metabolites [6][7][8][9]. All compounds listed tend to be adsorbed to suspended particulate matter and thus might contribute to sediment contamination.…”
Section: Introductionmentioning
confidence: 71%